2017
DOI: 10.1016/j.jaac.2017.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Autism Spectrum Symptoms in a Tourette’s Disorder Sample

Abstract: Objective Tourette syndrome (TS) and autism spectrum disorder (ASD) share clinical features and possibly an overlapping etiology. This study: 1) examined ASD symptom rates in participants with TS and 2) characterized the relationships between ASD symptom patterns and TS, obsessive-compulsive disorder (OCD), and attention-deficit/hyperactivity disorder (ADHD). Method Participants with TS (n = 535) and their family members (n =234) recruited for genetic studies reported TS, OCD, and ADHD symptoms and completed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
47
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 42 publications
4
47
1
2
Order By: Relevance
“…In children and adolescents with TS, social responsiveness has been shown to be impaired, which suggests autistic-like symptoms in those patients [ 205 ], and is consistent with the study of Darrow et al [ 223 ]. However, those social impairments could be attributable to specific tics, comorbid disorders or cognitive impairments rather than TS itself.…”
Section: A Review Of Neuropsychological Functioning In Tssupporting
confidence: 84%
See 2 more Smart Citations
“…In children and adolescents with TS, social responsiveness has been shown to be impaired, which suggests autistic-like symptoms in those patients [ 205 ], and is consistent with the study of Darrow et al [ 223 ]. However, those social impairments could be attributable to specific tics, comorbid disorders or cognitive impairments rather than TS itself.…”
Section: A Review Of Neuropsychological Functioning In Tssupporting
confidence: 84%
“…Research in these domains has been particularly flourishing in recent years. Contemporary data on social cognition suggest slight impairments in this domain, mostly in emotional regulation [ 91 , 224 , 227 ] and social interactions [ 205 , 223 ] in TS patients. In regards to school difficulties, recent research suggests that learning difficulties and disabilities could occur more frequently in children with TS, but more research in this domain is needed to make strong assumption.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…oppositional defiant disorder, conduct disorder), learning disorders, sleep disorders, impaired social cognition and sensory processing difficulties . Autistic spectrum disorder (ASD) has been diagnosed in 5–15% of TS cohorts . A recent study using the Social Responsiveness Scale found that 23% of TS patients met ASD criteria, although this was primarily due to higher scores in the repetitive and restricted behaviours subscale, highlighting the importance of social communication impairments in making an ASD diagnosis in a child with TS .…”
Section: Comorbiditiesmentioning
confidence: 99%
“…9 Autistic spectrum disorder (ASD) has been diagnosed in 5-15% of TS cohorts. 11 A recent study using the Social Responsiveness Scale found that 23% of TS patients met ASD criteria, although this was primarily due to higher scores in the repetitive and restricted behaviours subscale, highlighting the importance of social communication impairments in making an ASD diagnosis in a child with TS. 11 Self-injurious behaviour occurs in a minority of TS patients, particularly in those who are highly obsessional and those with ASD.…”
Section: Comorbiditiesmentioning
confidence: 99%